The Influence of Small-Sided Games and Floaters Intervention on Physical Components of Soccer Players - MA, Midhun Kumar; G, Vinod Kumar; W, Vinu (Physical Education Theory and Methodology, 2025)
Background. In soccer, numerical superiority enhances the effectiveness of both offensive and defensive actions performed by players. To improve the performance of the players, small-sided games (SSGs) with numerical inferiority and superiority should be incorporated into training sessions. Objectives. The study aimed to evaluate the effect of a 12-week training program using floaters and small-sided games (SSGs) on the physical performance of soccer players. Materials and methods. A total of 52 soccer players participated in the study. The age ranged from 14 to 16 years. The participants were divided into small-sided games with the floater’s group (Group I, SSGs+Floaters, n = 26) and the control group (Group II, n = 26). A 12-week program of small-sided games with floaters intervention was completed by the experimental group, who trained five days per week. Each session lasted 90 minutes, including warming up, small-sided games incorporating floaters intervention, lead-up games, and cooling down. The control group did not practice the floaters training program. The Yo-Yo intermittent recovery level 1 test was used to assess maximal aerobic endurance (VO2max), the Sargent jump test measured leg explosive strength, the Illinois agility test assessed soccer-specific agility, and the 50-meter sprint test evaluated speed. A paired t-test was conducted to measure the within-group differences from pre- to post-test, while the effects of the training were evaluated using ANCOVA and effect size analysis. Results. The results indicated that small-sided games with floaters intervention significantly improved maximal aerobic endurance, leg explosive strength, and agility except speed. In contrast, the control group did not demonstrate similar improvements. Furthermore, there was a significant difference between the experimental and control groups in maximal aerobic endurance, leg explosive strength, and agility, although speed did not show such a difference. Conclusions. The findings of this study suggest that implementing small-sided games with floaters intervention can effectively enhance physical performance variables in junior soccer players.